Biodegradation Of Oil Palm Empty Fruit Bunches In Liquid Fermentation Using Mixed Microorganisms From Palm Oil Mill Effluent - Abd. Halim, Nor Fadilah (2008)

(untitled)
The degradation of oil palm empty fruit bunch (EFB) in liquid fermentation using microbial complex obtained from palm oil mill effluent (POME) under non-sterile condition was investigated in the present study. A control study using carboxymethylcellulose (CMC) as substrate to examine the cellulose degradation ability of the microbial complex from POME. The effects of the operating parameters of fermentation; size of inoculum, aeration rate, pH and substrates concentration on the degradation of EFB and CMC were studied. The effectiveness of mixed microorganisms from POME on the biodegradation of pure cellulose EFB was also determined in this study. The degradation was performed at agitation speed of 150 rpm in a 10 liter bioreactor under various above mentioned process parameters for a 10 day period. The evolution of dry matter (DM) and Chemical oxygen demand of solids (CODs) were used to measure the performance of the non-sterile liquid fermentation process on the solid degradation of EFB and CMC. An optimized biodegradation process of EFB and CMC by mixed microbes from POME was performed at the end of this study. The selection of the parameters for the optimized biodegradation process was based on those that provided the best degradation during the optimization study.The study of the effect of inoculum size on the biodegradation of CMC showed that 300 mL/L is the optimal condition for both DM and CODs reduction. The DM and CODs reduction of EFB was slightly increased (< 7%) as the inoculum size increase to 450 mL/L but the biodegradation rate of CMC was reduced by more than 50% (in term of CODs reduction). Hence 300 mL/L was chosed as optimal inoculum size for the study of the optimized biodegradation of EFB and CMC. The effect of aeration rate on the reduction of DM and CODs was different. The highest DM reduction was achieved at 1.0 vvm, while the highest CODs reduction was achieve at 0.5 vvm for both EFB and CMC biodegradation study. As a result aeration rate of 0.5 vvm was selected as the optimal condition for further study. The effect of pH on the reduction of DM and CODs was somewhat different. Generally lower pH give a better DM reduction for both EFB and CMC biodegradation studies. However, the highest CODs reduction was achieved at pH 4.5 and 5.0 for the biodegradation study of EFB and CMC, respectively. The pH 5.0 was selected for the optimized study as the highest specific reduction rates of both DM and CODs were achieved at this pH value. The reduction of DM and CODs was different when changing substrate concentration for the biodegradation studies of EFB and CMC. The highest DM reduction was achieved at the substrate concentration of 10 g/L for both EFB and CMC. The highest CODs reduction was achieved at substrate concentration of 20 and 25 g/L for the biodegradation studies of EFB and CMC, respectively. The substrate concentration of 15 g/L was selected for optimized biodegradation study due to the highest specific rates of reduction for both DM and CODs were achieved of this value of substrate concentration. Optimized biodegradation studies of both EFB and CMC were conducted at the inoculum size of 300 mL/L, aeration rate of 0.5 vvm, pH of 5 and substrate concentration of 15 g/L. The DM and CODs reduction for EFB were respectively 70% and 30% higher than that of CMC. The microbial analysis revealed that more fungus and yeast population were found during the middle stage of EFB biodegradation compared to that of CMC. Bacteria population has dominated the fermentation medium of CMC. This may explained the higher level of biodegradation that has been achieved in the EFB experiment. Yeast and fungus has a better ability to degrade the complex structure of biomaterial such as lignin, hemicellulose and cellulose found in the EFB. The degradation of EFB can be expeditiously carried out to achieve about 57% DM reduction under fermentation conditions of inoculum size of 300 mL/L mixed culture microorganisms, aeration rate of 1.0 vvm, pH 6.0 and substrate concentration of 15 g/L. The highest DM reduction of CMC, 31.11% was achieved under 150 mL/L of inoculum size, 0.5 vvm aeration rate, pH 6.0 and substrate concentration of 15 g/L. In conclusion, the biodegradation of EFB and CMC was affected differently by the parameters being studied due to the presence of different type of microbes in the middle stage of biodegradation process.